2022
DOI: 10.2196/40637
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Cognitive Behavioral Therapy for Postsecondary Students: Randomized Factorial Trial for Examining Motivational Interviewing and Booster Lessons

Abstract: Background Internet-delivered cognitive behavioral therapy (ICBT) can improve access to mental health care for students, although high attrition rates are concerning and little is known about long-term outcomes. Motivational interviewing (MI) exercises and booster lessons can improve engagement and outcomes in face-to-face cognitive behavioral therapy. Objective This study aimed to examine the use of pretreatment MI exercises and booster lessons in ICBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…These manipulated various aspects of the treatment format reported mostly null results with small effect sizes. In single trials, small moderating effects were reported for therapist guidance, app recommendations and pretreatment motivational interviewing 70 96. In other trials, null results were, however, also reported for guidance and motivational interviewing 51 80…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These manipulated various aspects of the treatment format reported mostly null results with small effect sizes. In single trials, small moderating effects were reported for therapist guidance, app recommendations and pretreatment motivational interviewing 70 96. In other trials, null results were, however, also reported for guidance and motivational interviewing 51 80…”
Section: Resultsmentioning
confidence: 96%
“…In the 57 included trials, 21 795 participants were randomised 46–102. Arms were as follows: 83 internet-delivered transdiagnostic psychological treatments, 36 rudimentary controls, 8 attention/engagement controls and three other bona-fide treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Web-delivery was the most frequent delivery method for asynchronous interventions ( n = 9) followed by app-based interventions ( n = 1; Ravaccia et al, 2022 ), and combination-delivered interventions ( n = 1; Hennemann et al, 2022 ). Solely asynchronously guided support was provided through email ( n = 1; Juniar et al, 2022 ), SMS/text messages ( n = 1; Peynenburg et al, 2022 ), and other messaging functions built in to the intervention platform, such as chat functions ( n = 7). Partially asynchronous guided support ( n = 10) was provided through a mix of messaging (within platform or SMS) and phone calls ( n = 6), emails and phone calls/text ( n = 1; Stapinski et al, 2021 ), phone calls only (Radomski et al, 2020 ), emails (O’Connor et al, 2020 ), and other channels such as online support and community newsfeeds ( n = 1; van Doorn et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Use NR NR Mean intervention length 89.64 days ( SD = 67.87; range = 4–475) for SC-ONLY, 96.09 days ( SD = 133.44; range 3–1036) for SC + TX. On average, SC-ONLY and SC + TX participants used 15% of DHMI or viewed an average of 16.27 pages ( SD = 17.72; Range 0–101) and used an average of 3.88 tools ( SD = 4.98; Range 0–41) Efficacy = Yes Efficient = NR Peynenburg et al ( 2022 ) To examine effects of including pretreatment MI and a self-guided booster (UniWellbeing) offered 1-month after transdiagnostic iCBT for postsecondary students 1. Satisfaction (TSQ) NR High satisfaction (82.3% (158/193) with participants reporting they were ‘satisfied’ or ‘very satisfied’ with treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Motivational interviews before ICBT program may encourage participants to use the program for more days ( Soucy et al, 2021 ; Titov et al, 2010 ). On the other hand, motivational interviewing may not benefit all individuals equally ( Peynenburg et al, 2022 ). It is therefore important to restrict motivational interviews only to those who would benefit from them, in order to avoid an additional treatment burden.…”
Section: Discussionmentioning
confidence: 99%